Prenatal tobacco prevention and cessation interventions for women in low- and middle-income countries - Oncken, Cheryl A. (2010)
Although the prevalence of tobacco use is decreasing in many high-income countries, it is increasing in many low- and middle-income countries. The health and economic burden of increasing tobacco use and dependence is predictable and will have devastating effects in countries with limited resources, particularly for vulnerable populations such as pregnant women. We sought to review effective tobacco prevention and intervention strategies for decreasing tobacco use and secondhand smoke exposure before and during pregnancy in high-, middle-, and low-income countries. We reviewed several types of interventions, including population-level efforts (increasing tobacco prices, implementing tobacco control policies), community interventions, clinical interventions, and pharmacological treatments. A second purpose of this report is to present findings of an international expert working group that was convened to review the evidence and to establish research priorities in the following areas: (a) preventing the uptake and reducing tobacco use among girls and women of reproductive age; and (b) reducing tobacco use and secondhand smoke exposure among pregnant women. The working group considered the evidence on existing interventions in terms of burden of disease, intervention impact, intervention costs, feasibility of integration into existing services, uniqueness of the contribution, and overall feasibility. Finally, we present the working group´s recommendations for intervention research priorities.